2007
DOI: 10.1111/j.1442-2050.2007.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from salvage esophagectomy post definitive chemoradiotherapy compared with resection following preoperative neoadjuvant chemoradiotherapy

Abstract: Chemoradiotherapy (CRT) as a definitive treatment for esophageal cancer, is being used with increasing frequency and as a result, surgeons will be required to assess more patients who have residual or recurrent local malignancy. This article aimed to assess outcomes after esophagectomy following definitive CRT (dCRT) and compare any difference between them and patients who had preoperative neoadjuvant CRT (nCRT) using a similar regimen of chemotherapy. From a prospective database the details of patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…The pooled analysis of five studies (14)(15)(16)18,20), revealed a significant increased incidence of overall postoperative morbidity in the salvage group (POR =1.30; 95% CI, 1.00-1.67, P=0.046). There was no evidence of significant statistical heterogeneity (I HR, hazard ratio.…”
Section: Postoperative Morbidity (Figure 4)mentioning
confidence: 99%
See 2 more Smart Citations
“…The pooled analysis of five studies (14)(15)(16)18,20), revealed a significant increased incidence of overall postoperative morbidity in the salvage group (POR =1.30; 95% CI, 1.00-1.67, P=0.046). There was no evidence of significant statistical heterogeneity (I HR, hazard ratio.…”
Section: Postoperative Morbidity (Figure 4)mentioning
confidence: 99%
“…After screening, one further publication (23), was excluded as this institution published their outcomes in a follow-up publication, which was included in the analysis (16). Therefore, ten comparative studies were included in this pooled final analysis (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In total 1,906 patients were included, 563 in the salvage group and 1,343 in the NCRS group.…”
Section: Study and Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, salvage surgery is a highly invasive and complex treatment leading to increased morbidity (50-79%) and in-hospital mortality (7-22%) as compared with those after neoadjuvant CRTx, due to the adverse events of predominantly respiratory complications and anastomotic leakage (Chao et al, 2009;Nakamura et al, 2004;M. Nishimura et al, 2007;Oki et al, 2007;Smithers et al, 2007;Swisher et al, 2002;Tachimori et al, 2009;Tomimaru et al, 2006). These hospital mortality rates are obviously higher than those for esophagectomy in Japan reported from specialized centers (2%) (Tachimori et al, 2009) or the nationwide registry (5%) (The Japan Esophageal Society).…”
Section: Definitive Crtx For Resectable Ecmentioning
confidence: 41%
“…The incidence of postoperative mortality was assessed in a considerable number of studies [61][62][63][64][65], fewer assessed in-hospital mortality, and 30-day mortality was determined in two studies [66]. Values were higher in patients who were treated with salvage esophagectomy after deinitive chemoradiotherapy (23 patients-9.50%) than in patients who treated with planned esophagectomy after neoadjuvant chemoradiotherapy (29 patients-4.07%).…”
Section: Postoperative Outcomementioning
confidence: 99%